The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1590/s0101-81752001000400027
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphism in males of Zaops ostreum (Say) (Crustacea, Decapoda, Pinnotheridae)

Abstract: ABSTRACT. A case of dimorphism among the males of the pinnotherid crab, Zaops ostreum (Say, 1817), is reported. The morpho1ogical features ofthe two types ofmales are also given. KEY WORDS. Zaops ostreulIl, dimorphism, males A study being carried out to determine the diversity of carcinofauna of the estuaries ofthe State ofRio Grande do Norte has recorded Zaops ostreum (Say, 1817) associated with the oyster Crassostrea rhizophorae in the estuary near Macau , Rio Grande do Norte, Brazil. Though C. rhizophora is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
3
3
Order By: Relevance
“…During the dry season occurred a high decrease of non-ovigerous females (no non-ovigerous females found from September to December), indicating a reproductive peak during this season. Contrasting with the results obtained by Sankarankutty and Ferreira (2001) in C. rhizophorae at Macau Estuary (State of Rio Grande do Norte, Northeast Brazil), most of our occurrences were female-male couples (mean 79.29%) without isolated males and triple occupancy, while the previous authors reported lower female-male couples' rate (28,83%), as well as isolated males and triple occupancy (Sankarankutty and Ferreira, 2001). Nonetheless, no female-male couples were recorded on September at Barra de Catuama (this study) and Macau Estuary (Sankarankutty and Ferreira, 2001).…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…During the dry season occurred a high decrease of non-ovigerous females (no non-ovigerous females found from September to December), indicating a reproductive peak during this season. Contrasting with the results obtained by Sankarankutty and Ferreira (2001) in C. rhizophorae at Macau Estuary (State of Rio Grande do Norte, Northeast Brazil), most of our occurrences were female-male couples (mean 79.29%) without isolated males and triple occupancy, while the previous authors reported lower female-male couples' rate (28,83%), as well as isolated males and triple occupancy (Sankarankutty and Ferreira, 2001). Nonetheless, no female-male couples were recorded on September at Barra de Catuama (this study) and Macau Estuary (Sankarankutty and Ferreira, 2001).…”
Section: Discussioncontrasting
confidence: 92%
“…Contrasting with the results obtained by Sankarankutty and Ferreira (2001) in C. rhizophorae at Macau Estuary (State of Rio Grande do Norte, Northeast Brazil), most of our occurrences were female-male couples (mean 79.29%) without isolated males and triple occupancy, while the previous authors reported lower female-male couples' rate (28,83%), as well as isolated males and triple occupancy (Sankarankutty and Ferreira, 2001). Nonetheless, no female-male couples were recorded on September at Barra de Catuama (this study) and Macau Estuary (Sankarankutty and Ferreira, 2001). These results obtained in tropical environments highly contrast with results obtained by Christensen and McDermott (1958) at the Bay Shore Channel (USA), were reproductive seasons seem be rather accentuated, with distinct periods for double occupancy and prolonged declines on male abundances after copulation.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations